Strategi Bimbingan Manasik Haji Dalam Meningkatkan Pemahaman Ibadah Haji Pada Calon Jemaah Haji Di Kbihu Raudhatul Ulum Palembang - Silvi Dinda Agestia; Hidayat HT; Emi Puspita Dewi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the strategy of Hajj manasik guidance in improving the understanding of Hajj rituals among prospective pilgrims at KBIHU Raudhatul Ulum Palembang. This research employs a qualitative approach with a field research design. The data sources consist of primary and secondary data collected through interviews, observations, and documentation. Data analysis techniques include data reduction, data display, and conclusion drawing. The results indicate that the strategies implemented in Hajj manasik guidance include lectures, practical demonstrations, ritual simulations, and the use of visual and interactive media. In addition, instructors apply persuasive and communicative approaches to facilitate participants’ understanding. These strategies have proven effective in enhancing the understanding of prospective pilgrims, including their knowledge, practical skills, and mental readiness in performing Hajj rituals. Therefore, structured and systematic manasik guidance plays a significant role in preparing pilgrims to perform Hajj properly in accordance with Islamic teachings.